Czech Republic : Report on the Observance of Standards and Codes-Banking Supervision-Update. (IMF Staff Country Reports; Country Report ;, 2004)
The Czech government placed high priority on implementing and observing the international standards relevant for financial stability. The supervisory staff exhibited a high understanding of best international supervisory standards, policies, and practices. Nevertheless, the report noted significant weaknesses in laws governing debtor-creditor relations, inefficiencies in the judicial process, cumbersome administrative requirements, and low supervisory skills, and the need to audit computer-based systems and evaluate risk management systems. Enhancing the legal and regulatory framework is required to build up supervisory capacity, and to increase attention to supervisory coordination and cooperation.